Nutritional value of peanut haulm: effects on digestibility and on growth performance of sheep fed peanut hay or silage - Addah, W.; Ayantunde, Augustine A.; Larbi, Asamoah; McAllister, T.A. (2019)
Sun-drying is the main method of conserving peanut haulms in the tropics but it is challenging to field-dry and store in the rainy season due to nutrient losses, which could be reduced by ensiling. This study investigated the effects of conserving peanut haulm as hay or silage on growth performance of sheep. Peanut haulms were used to formulate 2 dietary treatments containing 450 g kg-1 DM each of hay or silage. Twenty West African Dwarf ram-lambs (29.7 ± 0.989 kg; mean ± SD) were randomly assigned to each dietary treatment in a completely randomized design. Dry matter intake of the silage-based diet was depressed (P = 0.053) by 117.9 g d-1 compared to that of the hay-based diet. Proteolysis as evidenced by the higher population of yeasts and concentrations of butyric acid and ammonia N in the silage as compared to hay, may have accounted for the poorer intake. Sheep fed the silage- vs hay- based diet exhibited lower (P = 0.012) average daily gains (38.8 vs. 81.8 g d-1) and poorer (P = 0.053) feed efficiency. Ensiling peanut haulms in the tropics without addition of exogenous soluble sugars may result in poor quality silages compared to sun-dried peanut haulms.